Physical fitness level of fifth grade students at Centong Elementary School, Gondang District, Mojokerto Regency in the new normal era - Puguh Satya Hasmara; Ilmul Ma'arif (Universitas Sebelas Maret, 2022)
This study aims to determine the level of physical fitness of students in the new noemal era. This research is a quantitative survey method with the aim of describing. The subjects in this study were the fifth grade students of SDN Centong, Gondang District, Mojokerto Regency, amounting to 34 students. The data analysis technique used descriptive statistics using percentages. The instrument used is the Indonesian Physical Fitness Test (TKJI), which consists of 5 test items, namely the 40-meter running test, the hanging elbow test, the 30-second lying down test, the upright jump test, and the last is the 600-meter endurance test. The results of this study are the level of physical fitness of 5th grade SDN Centong students in the medium category with the average cumulative score obtained by students is 16.